La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Closing the Gap: Impact & Representation of Indigenous, Black, and People of Colour Live Music Workers in Canada - Canadian Live Music Association (Canadian Live Music Association, 2022)

L’avenir. Les changements que les personnes répondantes souhaitent voir concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

L’état des choses. Le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Le suivi. Dénonciation, soutien et qui cause le préjudice? Concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision. - Aftermetoo (2021)
Keywords: Pas de lien web

Les dommages. Les répercussions sur les personnes survivantes du harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Principaux constats. Résultats de la toute première enquête sur le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Sur le terrain. La parole aux personnes survivantes. Suggestions écrites concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Do We Really Want to Keep the Gate Threshold That High? - Brooks, Grace; Pras, Amandine; Elafros, Athena; Lockett, Monica (Journal of the Audio Engineering Society, 2021)
Drawing upon the survey instruments of Lewis and Neville [1], Nadal [2], and Yang and Carroll [3], we conducted an online survey that captured experiences of discrimination and microaggressions reported by 387 recording engineers, producers, and studio assistants living in 46 different countries. Our statistical analyses reveal highly significant and systemic gender inequalities within the field, e.g., cisgender women experience many more sexually inappropriate comments (p < e-14, large effect size) and unwanted comments about their physical appearance (p < e-12, large effect size) than cisgender men, and they are much more likely to face challenges to their authority (p < e-13, large effect size) and expertise (p < e-10, large effect size). A comparison of our results with a study about women’s experiences of microaggressions within STEM academia [3] indicates that the recording studio workplace scores 33% worse on the silencing and marginalization of women, 33% worse on gender-related workplace microaggressions, and 24% worse on sexual objectification. These findings call for serious reflection on the part of the community to progress from awareness to collective action that will unlock the control room for women and other historically and systemically marginalized groups of studio professionals.

Prendre soin des paroles effacées - Brunette, Edith (Liberté. Art et politique., 2021)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

Black Minstrelsy on Canadian Stages: Nostalgia for Plantation Slavery in the Nineteenth and Twentieth Centuries - Thompson, Cheryl (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
Le blackface minstrelsy, qui a vu le jour dans le nord-est des États-Unis dans les années 1820 et 1830, mettait en scène des artistes blancs, principalement des hommes, qui franchissaient les frontières raciales en imitant des Afro-Américains avec la musique, l’humour et la danse prétendument « authentiques », courants dans les plantations du sud. Dans les années 1860, les Afro-Américains nouvellement émancipés se produisaient également sur scène en blackface. À la fin du XIXe siècle, cependant, les acteurs noirs ne se grimaient plus en noir, mais ils devaient toujours perpétuer les stéréotypes de la plantation. Ces troupes étaient dirigées par des directeurs noirs et blancs qui présentaient leurs spectacles comme « authentiques » et « nostalgiques ». Ces éléments du spectacle de minstrel noir — surtout ses représentations soi-disant « réelles » du Sud des États-Unis et de l’esclavage dans les plantations — ont trouvé un écho auprès du public canadien. Ils constituent donc une autre perspective d’approche — en dehors des politiques d’immigration et Jim Crow de facto — pour expliquer la présence du racisme et de la xénophobie anti-Noirs au Canada à la fin du XIXe siècle et au début du XXe siècle. En examinant le contenu de la minstrelsy noire, le rôle joué par les directeurs dans ses productions et la promotion dans les journaux, cet article soulève des questions sur l’étendue à laquelle les Canadiens ont été historiquement complices du dénigrement des Noirs.

College Boy (2013) de Xavier Dolan : pérenniser “le backward feeling” - Hakeem, Hasheem (Contemporary French Civilization, 2020)
En 2013, Xavier Dolan, cinéaste, acteur et metteur en scène québécois prolifique, réalise le vidéoclip College Boy, chanson du groupe de musique français Indochine qui s’articule autour d’un jeune garçon queer qui est victime d’homophobie dans un internat. Cet article propose une analyse de ce vidéoclip en se focalisant sur la mise en scène de la violence et des affects négatifs. Nous étudions d’abord le débat provoqué par la diffusion et la censure du clip en France. Ensuite, à partir de la théorie du “backward feeling” développée par Heather Love dans Feeling Backward: Loss and the Politics of Queer History (2007), nous analysons la manière dont la représentation de la violence dans l’œuvre de Dolan remet en question l’ordre hétéronormatif. Nous défendons la thèse qu’en s’attaquant de front aux institutions qui sont les véritables agents de la violence homophobe, College Boy contribue à la conservation archivistique de l’expérience queer et crée ainsi une possibilité d’émancipation face à l’hétéronormativité.

The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.

Avant-propos. Pour des musicien·ne·s organiques ? - McKinley, Maxime (Circuit, 2018)
Keywords: Inclure l'avant-propos ?

"The Canadian Inhabitants are Remarkably Fond of Dancing": Reading the African Musicians in George Heriot's Minuet of the Canadians (1807) - Nelson, Charmaine A. (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues--a group of established and up-and-coming artists, scholars, and cultural critics--argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History--an African Canadian Art History

Le hip-hop avec des gants blancs - Néméh-Nombré, Philippe (Liberté, 2018)
Réflexion sur la dépolitisation et l’éclaircissement du hip-hop lors de son passage dans la culture de masse.

“Come One, Come All”: Blackface Minstrelsy as a Canadian Tradition and Early Form of Popular Culture - Thompson, Cheryl (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues--a group of established and up-and-coming artists, scholars, and cultural critics--argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History--an African Canadian Art History

Les chemins de ma liberté - Simard, Nathalie (Éditions des Intouchables, 2015)

Le Lunatique, « Le temps du changement » : Intimidation, ostracisme et homophobie dans le milieu hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Le tout premier livre monographique et scientifique axé sur la culture Hip-Hop au Québec, rédigé par Kapois Lamort, historien spécialiste diplômé de l’Université du Québec à Montréal ( UQAM); cet ouvrage retrace les 35 ans d’existence du H.I.P.H.O.P. à travers la société québécoise de 1979 à 2015

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.

Listening to/at/with Marilyn Lerner’s "They’re All in Families" - McNeilly, Kevin (Critical Studies in Improvisation / Études critiques en improvisation, 2008)
Marilyn Lerner’s audio-art composition “They’re All in Families” (1998) re-works a sound clip from a virulently homophobic message left on an answering machine, turning hate-speech back on itself to expose the rhythms and textures of verbal violence.

C'était du spectacle! L'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Le quartier chaud de Montréal a fait couler beaucoup d'encre, mais sa culture de cabaret n'a jamais été examinée dans la perspective des artistes transsexuelles et travesties qui l'ont rendu si populaire. Par le biais des récits provenant des danseuses elles-mêmes, Viviane Namaste peint un portrait honnête de quatorze transsexuelles - danseuses, chanteuses, magiciennes ou effeuilleuses - et jette un regard dans les coulisses du monde dans lequel vivent et travaillent ces hommes devenus femmes. Les années soixante et soixante-dix ont été des décennies de changement social au Québec. C'était du spectacle! raconte l'histoire de la première génération de transsexuelles ayant subi une chirurgie d'inversion de sexe. Namaste examine les conditions de travail dans les cabarets, la prostitution, les abus de pouvoir des policiers à l'égard des transsexuelles, le rôle du crime organisé dans la vie nocturne de la ville et l'accès aux soins de la santé. C'était du spectacle! offre un rare survol de la culture urbaine de Montréal, présenté dans ses propres mots par l'une de ses plus importantes communautés artistiques.

Briser le silence. Nathalie - Vastel, Michel (Éditions Libre Expression, 2005)
Un livre attendu, celui de Nathalie Simard, une jeune femme courageuse qui est devenue le symbole de toutes les femmes abusées, dont Michel Vastel signera l’histoire. Un témoignage touchant écrit par un journaliste d’envergure qui racontera l’histoire d’une femme, mais aussi celle de sa famille et de son entourage tout au long des années où elle a travaillé dans le monde du spectacle. Il y sera question de son enfance, son adolescence, jusqu’au dénouement médiatique de son histoire qui a éclaté dans les journaux en 2004 et en 2005.